Kasih Setia Tuhan Dalam Perjanjian Lama Dan Relevansinya Bagi Orang Percaya Pada Masa Covid-19 - Sri Wahyuni Kusradi (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2020)
ABSTRAK _______________________________________________________________ Pada masa pandemic Covid-19 ini banyak orang menjadi kuatir akan masalah penghidupannya, masa depan keluarga, masyarakat, ekonomi, politik, pendidikan, kebudayaan yang berubah mengikuti dampak covid-19 ini. Hal tersebut juga dihadapi oleh orang Kristen, mereka dapat saja mempertanyakan di mana Tuhan pada masa pandemic ini. Tetapi ada satu pegangan yang teguh yang dapat menjadi penghiburan dan kekuatan bagi orang percaya, yaitu Kasih setia Allah yang akan memberikan jaminan kehidupan orang percaya pada masa pandemic ini. Di mana dalam Perjanjian Lama kasih setia Tuhan telah dinyatakan kepada bangsa Israel dari sejak jaman Adam telah diikatkan dari keturunan ke keturunan yang diikat melalui sebuah perjanjian yang tidak setara antara Allah dengan umat pilihan, didasarkan pada kemurahan hati Allah yang masih berlaku hingga sampai kini. Untuk itu penulis akan menggunakan metode Untuk memaparkan tujuan penulisan ini maka penulis menggunakan metode deskriptif teologis yang akan mencermati teks-teks Alkitab mengenai kasih setia, memperhatikannya berdasarkan konteks sejarah untuk menemukan bagaimana prinsip-prinsip kasih setia Tuhan itu dinyatakan kepada generasi ke generasi Israel. Dari penelitian itu akan diperoleh makna teologis tentang penyataan-penyataan kasih setia Tuhan di sepanjang sejarah Israel dalam Perjanjian Lama. Dalam penemuan makna-makna theologis maka topic ini dapat dikorelasikan dengan keadaan pada masa pandemic sekarang ini. Bagaimana bentuk penyataan kasih setia Tuhan dan bagaimana orang percaya pada masa kini harus menyikapinya. Saat orang percaya memahami dan terus memegang perjanjian kasih setia Tuhan maka iman kepada Allah akan terus semakin teguh sekalipun di saat penderitaan pada masa covid-19 ini melanda. Kata Kunci: Kasih Setia Tuhan, Perjanjian Lama, Covid-19 ABSTRACT _______________________________________________________________ The second abstract is written in English. During the Covid-19 pandemic, many people became worried about their livelihood problems, the future of their families and how to manage their lives. This happens because the economic crisis is threatening, family incomes are declining or unstable, health is not guaranteed, the ease with which social problems occur makes life uneasy. The same thing can be faced by Christians. If they do not have a strong faith, Christians will also experience shocks of faith. But there is one firm hold that can be a comfort and strength to believers, which is God's character. God's loyal love will provide assurance for the life of believers in this pandemic. Where in the Old Testament the love of God has been shown to the Israelites from the time of Adam has been tied from generation to generation. God's loyal love bound through an unequal covenant between God and the elect, which is based on God's generosity. God's lovingkindness that was expressed in various forms during the Old Testament times and also which is still in effect today. For this reason, the author will use the method. To explain the purpose of this writing, the author uses a theological descriptive method that will examine the biblical texts regarding of The Kindness og God as stated in the Old Testament, paying attention to it based on the historical context to find how the principles of The Kindness of God are expressed. in various forms from generation to generation of Israelis. From this research, theological meaning will be obtained about the revelations of The kindness of God throughout the history of Israel in the Old Testament. In the discovery of theological meanings, this topic can be correlated with the situation in the current pandemic. What is the present form of expression of The kindness of God and how today's believers should react to it. When believers today understand and continue to hold onto God's covenant of loyal love, faith in God will continue to be stronger even when suffering during the Covid-19 era hits. Keywords: Kindness of God, Old Testament, Covid-19